Nutritional Education and Community Health : Some Cases and Problems - Yagasaki, Nobuko (Journal of the Japanese Association for Cerebro-cardiovascular Disease Control, 1991)
Nutritional education has been presented in various forms for varied purposes and its importance is increasingly recognized. In order to clarify some of the problems in contemporary nutritional education, and areas for improvement, the following three different nutritional guidance programs were studies : (1) a program for reduced salt intake in a rural community with high mortality from cerebrovascular diseases ; (2) weight control program for obese females at a weight control clinic in Tokyo ; and (3) nutritional guidance for males employed in a large company in metropolitan Tokyo. Community nutritional education begins with proper planning with clear purposes and goals with consideration given to manpower needs such as councelors, budget, and facilities. Results are often evaluated by behavioral approaches which examine changes in the eating behavior of the subjects. Effective nutritional education is a long-term process in which setting of goals, choice of methods, and evaluation of results are repeated in that order. Programs must be conducted in established facilities with physicians and public health nurses and under the initiative of nutritionists. High participation rates and continuity must be maintained by maintained by motivating participants, accurate information provided, consciousness levels for health and disease prevention increased, and diet patterns as well as the living environment in general should be improved. Mutual confidence between the parties involved is definitely a factor in increasing effectiveness of such educational programs.